2011
DOI: 10.14712/18059694.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

Late Onset of Aspergillus Aortitis Presenting as Femoral Artery Embolism Following Coronary Artery Bypass Graft Surgery

Abstract: Summary: Aspergillus sp. are ubiquitous mould infections and in most patients, the source is presumed to be air-borne infections during surgical procedures. Prevention of these infections requires special attention of ventilation systems in operating rooms. Post-operative aspergillosis occurs mainly in immunocompromised patients as well as those who receive corticosteroids temporarily. We report a case of a 71-year-old immunocompromised patient who developed multiple lower limb embolisms due to Aspergillus nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…6 Similarly, a case of Aspergillus niger aortitis presented as lower limb embolisms 9months after CABG. 7 Likewise, acute aortic occlusion from a saddle embolus originating from Aspergillus niger aortitis happened 4months after aortic valve replacement. 8 Another immunocompetent patient had embolization to the cerebral artery and cubital artery three years following CABG.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similarly, a case of Aspergillus niger aortitis presented as lower limb embolisms 9months after CABG. 7 Likewise, acute aortic occlusion from a saddle embolus originating from Aspergillus niger aortitis happened 4months after aortic valve replacement. 8 Another immunocompetent patient had embolization to the cerebral artery and cubital artery three years following CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic infection has also been described after cardiovascular surgery for valvular replacement [9] , [14] , [16] , aortocoronary bypass [9] , [12] , [13] , and replacement of the aorta for aortic dissection [15] . Aspergillus aortitis includes ascending aortic pseudoaneurysm [9] , aortic aspergilloma with supravalvular aortic stenosis [12] , and fungal ascending aortic aneurysm [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Aortic infection caused by Aspergillus , including infection in immunocompromised hosts [1–8] and after cardiovascular surgery [8] , [9] , [12] , [13] , [14] , [15] , [16] , is a rare event. Aspergillus infection in immunocompromised hosts can occur in patients with hematologic disorders [1–5] , acquired immunodeficiency syndrome [6] , or immunosuppression following kidney or heart transplant [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Noordally SO et al reported a case of postoperative Aspergillus niger aortitis in an immunocompromised patient presenting as femoral artery embolism. 7 Rana M et al observed a very interesting case of embolic Aspergillus endophthalmitis from the hematogenous spread of Aspergillus infection from aortic root eight months following composite aortic root replacement in a young immunocompetent person for severe aortic regurgitation and dilated ascending aorta. 8 In the present case Aspergilli could have gained entry from the environment during surgery.…”
Section: Disucssionmentioning
confidence: 99%